THE CORRELATION BETWEEN SMARTPHONE USE AND READING ACTIVITIES OF UNIVERSITY STUDENTS - Renyaan, Meske Maria; Rettob, Aloysius; Maukar, Merlin (SoCul: International Journal of Research in Social Cultural Issues, 2022)
This research aims to find out whether or not there is a correlation between smartphone use and students reading activities This research is conducted at English Education Department Faculty of Language and Arts Manado State University The method used in this research is qualitative method Data collection in this research is a questionnaire that is distributed to 27 students The result of this research shows data based on the variables smartphone use and reading activities The data from this research were displayed in percentage form The result of this research shows scores of each variable 87 96 for X variable and 74 23 for Y variable The researchers conclude that there is a correlation between these two variables because the difference in percentage scores between these two variables which is not too large which indicates that reading activities using smartphone is an activity that can attract students to read more Therefore both have a positive correlation because the two variables have increased in which respondents use smartphone for reading activities due to several considerations for example the simple form of a smartphone and easy to carry and use in a comfortable position depends to the wishes of the respondents and also the low price of a smartphone so the smartphone is not difficult to get < p>